Reducing Dollarization in the Caucasus and Central Asia - Cakir, Selim (IMF Working Papers; Working Paper, 2022)
Declining but still high dollarization rates in the Caucasus and Central Asia (CCA) region affect macroeconomic stability, monetary policy transmission, and financial sector development. Although several studies have investigated the dynamics of dollarization in the CCA, the relative roles of macrofinancial policies and financial market development in the de-dollarization process have not yet been assessed empirically. This paper takes stock of de-dollarization efforts and explores the short-term drivers of financial de-dollarization in the CCA region. It highlights that there remains significant scope to further reduce dollarization through continued progress in strengthening macroeconomic policy frameworks and in developing markets and institutions.